Ответы и объяснения

2013-08-09T00:09:01+04:00
(x^2 + 6x)^2 + 2(x + 3)^2 = 81\\ (x^2 + 6x)^2 + 2(x^2 + 6x+9) = 81 \\ \Pi ycmb\ x^2+6x=t\\
t^2+2(t+9)=81\\ t^2+2t-63=0\\ t_1=-9,\ t_2=7\\
x^2+6x=-9\ u \lambda u\ x^2+6x=7\\
x^2+6x+9=0\ u \lambda u\ x^2+6x-7=0\\
x_1=-3,\ x_2=-7,\ x_3=1
Ответ: -7; -3; 1.

(x^2 + 2x)^2 - (x+1)^2 = 55\\ (x^2 + 2x)^2 - (x^2+2x+1) = 55\\ x^2+2x=t\\ t^2-(t+1)=5\\
t^2-t-6=0\\ t_1=-2,\ t_2=3
x^2+2x=-2\ u \lambda u\ x^2+2x=3\\ x^2+2x+2=0\ u \lambda u\ x^2+2x-3=0
решений нет           x_1=-3,\ x_2=1
Ответ: -3; 1.